Integrating Financial, Marketing, and Management Information Systems to Navigate Plastic Packaging Cost Volatility: Evidence from Food and Beverage MSMEs in Jabodetabek, Indonesia - Nunung Wulan Sari; Siti Masrokhah; Anini Nihayah; Rengga Kusuma Putra; Arif Hadi Prasetyo (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2026)
The volatility of plastic packaging costs poses a serious challenge to the sustainability of food and beverage MSMEs because it directly impacts the production cost structure, product price stability, and business profitability. This condition encourages the importance of integrating financial, marketing, and management information systems as an adaptive strategy to improve MSME business resilience. This study aims to analyze the effect of integrating financial, marketing, and management information systems on the ability of MSMEs to overcome plastic packaging cost volatility, as well as to examine the mediating role of decision-making quality. The study used a quantitative approach with a survey method of 300 food and beverage MSMEs in the Jabodetabek area. Data collection techniques were carried out using a five-point Likert-scale questionnaire and analyzed using IBM SPSS Statistics through multiple linear regression analysis and path analysis. The results show that the integration of financial, marketing, and management information systems has a positive and significant effect on the ability of MSMEs to cope with plastic packaging cost volatility. The quality of decision-making was also shown to significantly mediate this relationship. This study implies that digital transformation based on information systems integration is an important strategy in improving operational efficiency, business adaptability, and resilience of MSMEs in situations of production cost uncertainty.